2008
DOI: 10.1111/j.1572-0241.2008.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Clinical, Serological, and Histopathological Features of Celiac Disease

Abstract: At initial diagnosis, CD shows age-related differences, which consist of more evident clinical and histological features in children. Furthermore, IgA TTGA levels correlate both with the degree of villous atrophy and with the patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 31 publications
10
75
1
6
Order By: Relevance
“…These findings correlate well with the more-severe villous atrophy and higher titers of CD-specific Abs in this group, as measured by almost all assays. Similar differences in histological features, clinical findings, and Ab titers between younger (Յ2-year-old) and older (Ͼ2-year-old) children were recently reported by Vivas et al (35). Our findings are in agreement with those of that group and others (14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings correlate well with the more-severe villous atrophy and higher titers of CD-specific Abs in this group, as measured by almost all assays. Similar differences in histological features, clinical findings, and Ab titers between younger (Յ2-year-old) and older (Ͼ2-year-old) children were recently reported by Vivas et al (35). Our findings are in agreement with those of that group and others (14).…”
Section: Discussionsupporting
confidence: 93%
“…Borderline and weak-positive results were considered positive for calculating sensitivity, specificity, PPV, NPV, and test efficiency. The participating children were divided into CD positives and negatives according to biopsy results, which are considered the gold standard for diagnosis of CD (15,17,20,26,33,35,37). Several of the clinical indications listed were more noticeable in the biopsy-negative group, namely, failure to thrive and other high-risk characteristics that might imply CD, such as diabetes mellitus type 1, hypertransaminasemia, and IgA deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that classic clinical malabsorption pattern is frequently observed in children during diagnosis, while classical symptoms occur in less than 25% of adult cases [12] . Table 1 contains an overview of different clinical manifestations in CD according to the presentation age.…”
Section: Symptomatologymentioning
confidence: 99%
“…In addition, the presence of intraepithelial lymphocytosis and/or villous atrophy and crypt hyperplasia of smallbowel mucosa, and clinical remission after withdrawal of gluten from the diet, are also used for diagnosis antitransglutaminase antibody (tTGA) titers and the degree of histological lesions inversely correlate with age [12] . Thus, as the age of diagnosis increases antibody titers decrease and histological damage is less marked.…”
Section: Diagnosismentioning
confidence: 99%
“…Studies on the role of the gut microbiota in CD pathophysiology are still in their early stages. The main findings related to microbiota composition in CD subjects are summarized in Table 1. CD is a common disorder in both children and adults (21). Nevertheless, our knowledge about the intestinal microbiota of adults with CD is still sparse.…”
Section: Microbiota and CDmentioning
confidence: 99%